Determination of electroosmotic and electrophoretic mobility of DNA and dyes in low ionic strength solutions. Issue 5 (15th September 2017) - Lallman, Joshua; Flaugh, Rachel; Kounovsky‐Shafer, Kristy L.
Abstract: Nanocoding, a genome analysis platform, relies on very low ionic strength conditions to elongate DNA molecules up to 1.06 (fully stretched DNA = 1). Understanding how electroosmotic and electrophoretic forces vary, as ionic strength decreases, will enable better Nanocoding devices, or other genome analysis platforms, to be developed. Using gel electrophoresis to determine overall mobility (includes contributions from electrophoretic and electroosmotic forces) in different ionic strength conditions, linear DNA molecules (pUC19 (2.7 kb), pBR322 (4.4 kb), ΦX174 (5.4 kb), and PSNAPf‐H2B (6.2 kb)) were analyzed in varying gel concentrations (1.50, 1.25, 1.00, 0.75, and 0.50%). Additionally, buffer concentration (Tris‐EDTA, TE) was varied to determine free solution mobility at different ionic strength solutions. As ionic strength decreased from 13.8 to 7.3 mM, overall mobility increased. As TE buffer decreased (< 7.3 mM), overall mobility drastically decreased as ionic strength decreased. Rhodamine B dye was utilized to determine the electroosmotic mobility. As the ionic strength decreased, electroosmotic mobility increased. The experimental electrophoretic mobility was compared to theoretical considerations for electrophoretic mobility (Pitts and Debye‐Hückel‐Onsager). Electroosmotic forces decreased the overall mobility of DNA molecules and bromophenol blue migration in a gel matrix as ionic strength decreased.